Protocol for the intracerebral injection of AAV-α-synuclein plus poly(ADP-ribose) to generate a Parkinson’s disease monkey model - Shuyi Liu; Wei Si; Zhengbo Wang (STAR Protocols)
Summary: The lack of an etiologic Parkinson’s disease (PD) model in non-human primates has inhibited our understanding of the disease and the development of therapies. Here, we present a protocol for generating a PD model in Macaca fascicularis. We describe steps for localizing the substantia nigra and striatum using magnetic resonance imaging (MRI). We then detail a technique for the intracerebral administration of adeno-associated virus (AAV)-mediated overexpression of α-synuclein into the substantia nigra plus the injection of poly(ADP-ribose) (PAR) into the striatum.For complete details on the use and execution of this protocol, please refer to Liu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.